An integrated model system for coastal flood prediction with a case history for Walcott, UK, on 9 November 2007. Issue 3 (4th November 2012) - Stansby, P.; Chini, N.; Apsley, D.; Borthwick, A.; Bricheno, L.; Horrillo‐Caraballo, J.; McCabe, M.; Reeve, D.; Rogers, B.D.; Saulter, A.; Scott, A.; Wilson, C.; et al.
Abstract An integrated model system is based on downscaling from climate models, to wave climate and continental shelf models for tides and surge, to coastal models for waves and water levels, to beach levels and overtopping of sea defences and inundation. Present operational practice in the UK is described. The model system is applied to the prediction of flooding at Walcott on 9 November 2007. Inundation levels are predicted in reasonable agreement with those at certain residential properties in Walcott as reported by the occupants. The effect of time‐varying and time‐averaged overtopping discharge is considered. Sensitivity of overtopping and inundation to uncertainties in nearshore wave height and water level is analysed, with the greatest sensitivity being to water level. Extreme joint probability analysis is undertaken, showing the event to be close to a 1 in 100‐year event. Finally, the effects of different rates of sea level rise and a climate change scenario are investigated for 2100; the simulations indicate that the return period of the equivalent 2007 event could reduce to less than 2 years with a 0.5m sea level rise.